Respuesta en el rendimiento del cultivo de arroz (oryza sativa) con fertilizante químico y biofertilizante (azolla anabaena) en el cantón macará, provincia de Loja -Ecuador - Celi Cartagenova, María de los Ángeles (2022)
The purpose of this work was to know the performance of the rice cultivation with the application of Azolla anabaena biofertilizer and chemical fertilizer in Macara canton, Loja province in the months of May to October 2021. Some evaluations were carried out to know the yields obtained in the field. The physical and chemical conditions were determinated through soil analysis, both in pre-sowing and post-harvest term. In addition, an analysis of the production costs of the different treatments was determined. Due to the use of T3 (chemical fertilization), 3 variables were obtained with higher results related to grain length, weight of 100 g and grain productivity and 5 variables with higher averages in the application of T2 (Azolla anabaena) associated to the height of the plant, panicle length, kernel width, kernel shape and percentage of fertile ear. The tests carried out by means of the soil analysis showed that Azolla anabaena fulfills a very important function to increase percentages greater than the nutritional elements (N, P, K) required by the crop. In addition, the economic analyzes with chemical fertilization had a greater investment in the total cost but a lower cost benefit, however, with the use of Azolla anabaena, it achieved the opposite of T3 (chemical fertilization) with a benefit / cost of 2.08 dollars of utility. for growing rice. Key words: rice, Azolla anabaena, chemical fertilizer